Uberworked and underpaid how workers are disrupting the digital economy - Scholz, Trebor (Cambridge, United Kingdom Polity Press, 2017)
"This book is about the rise of digital labor. Companies like Uber and Amazon Mechanical Turk promise autonomy, choice, and flexibility. One of network culture's toughest critics, Trebor Scholz chronicles the work of workers in the "sharing economy," and the free labor on sites like Facebook, to take these myths apart. In this rich, accessible, and provocative book, Scholz exposes the uncaring reality of contingent digital work, which is thriving at the expense of employment and worker rights. The book is meant to inspire readers to join the growing number of worker-owned "platform cooperatives," rethink unions, and build a better future of work. A call to action, loud and clear, [this book] shows that it is time to stop wage theft and "crowd fleecing," rethink wealth distribution, and address the urgent question of how digital labor should be regulated and how workers from Berlin, Barcelona, Seattle, and Säao Paulo can act in solidarity to defend their rights."--Amazon.com.
Introduction: Why digital labor now? -- Waged labor and the end of employment -- Playbor and other unpaid pursuits -- Vocabulary -- Crowd fleecing -- Legal gray zones -- On selective engagement -- The rise of platform cooperativism -- Epilogue.
Includes bibliographical references and index.
Keywords: Information technology -- Economic aspects; Information technology -- Social aspects; Social media -- Economic aspects; Labor; Electronic commerce -- Social aspects; Internet industry